(untitled) (Research, Society and Development, 2021)
This study has as objective to describe the clinical profile and therapeutic management of HELLP syndrome. The study has used as method an integrative literature review, developed through a search in the Pubmed database using the crossings of the descriptors in English “HELLP syndrome”, “complications”. To evaluate the research problem and its stratification, the PVO strategy was used. The strategy previously mentioned allowed us to formulate the following guiding question: What are the clinical manifestations of HELLP syndrome, and how does therapeutic management work? The pathophysiology of the disease is not known yet. However, it is believed to be caused by placental insufficiency and generalized endothelial dysfunction. Vague presentation is common; hypertension and proteinuria that characterize preeclampsia are usually absent when HELLP syndrome presents. It can present with nonspecific signs and symptoms, none of which are diagnostic and in most cases asymptomatic, but with symptoms such as persistent hyperreflexia, headache, confusion, abdominal pain, nausea and vomiting. Misdiagnosis and late recognition of HELLP syndrome are common due to its vague and variable presentation. When HELLP syndrome is identified, childbirth is necessary to avoid catastrophic maternal and neonatal outcomes. The identification of baseline parameters predictive of disease progression is, therefore, of great importance to define which obstetric approach should be prioritized.